PO 96 - A difficult airway challenge – case report - Matos Silva, Mafalda; Romano Ribeiro, Carolina; Seco Vaz, Inês; Serôdio, Paula; Dourado, Cláudia (Journal of the Portuguese Society of Anesthesiology, 2023)
x